Pengaruh Kepercayaan dan Citra Lembaga Terhadap Minat Donatur Membayar ZIS (Zakat, Infaq dan Shadaqah) di Lembaga Amil Zakat Ummul Quro (Laz-Uq) Jombang - Risalatul Muawanah (BIMA : Journal of Business and Innovation Management, 2019)
This study aims to determine the influence of trust and image of the institution, both partially and simultaneously on the interest of donors to pay ZIS (Zakat, Infaq and Sadaqah). This research is categorized as quantitative research using a questionnaire as an instrument. The population in this study were irregular donors who distributed ZIS worship at the Jombang Amil Zakat Institute (LAZ-UQ) Jombang. Samples taken as many as 74 respondents were determined by incidental sampling technique. The analysis technique used is multiple regression using SPSS version 16 as the test tool. The results of this study indicate that: (1) the trust variable has a positive effect on the interest of donors with t-count of 4.479> t-table 1.665 and the significance level of 0.000. (2) the institutional image variable has a positive effect on the interest of donors with a t-count value of 3,122> t-table 1,665 and a significance level of 0,000. (3) the trust and institutional image variables, simultaneously have a positive effect on the interest of donors with an F value of 43.293> F value of 0.312 table and a significance level of 0.000.